Congeneric savanna-forest species have similar reproductive phenologies - de Oliveira, João Pedro Machado [UNESP]; Massi, Klécia Gili [UNESP]; Rossatto, Davi Rodrigo [UNESP] (Elsevier, 2022)
The time for flowering and fruiting in plants is mainly influenced by environmental factors. Plant species that are subject to different environmental conditions, but phylogenetically close, such as forest and savanna congeneric species pairs growing in forest-savanna transitions in the Neotropics, can be comparatively studied to isolate the effects of the environment from phylogenetic influences. Thus, we performed a comparative study of flowering and fruiting start and duration, as well its relationships with dispersal modes and canopy phenology, analyzing herbarium data for 25 congeneric species pairs from different families, each containing at least one savanna and one forest species. We examined species phenological patterns using digitized specimens from one of the most comprehensive digitized plant datasets in Brazil, the SpeciesLink. We found savanna species having shorter flowering duration (2–5 months) in comparison with forest (3–8 months) congeneric species. Congeneric pairs presented similar reproductive phenological responses for all other studied traits. We found that dispersal mode played an important role in determining fruiting start and duration, while flowering and fruiting start were explained by leaf deciduousness. Although there were many phenological similarities between savanna and forest species, there were differences in flowering duration between savanna and forest species in some congeneric pairs.
Keywords: Cerrado sensu stricto; Flowering; Fruiting; Gallery forest; Phenology